Analyzing the Impact of Brand Image on Purchasing Decisions for Imitation Fashion Products - Khoirunnisa Syuhadah Umanah T; Sri Listiani; Ernita Maulida (Universitas Negeri Semarang, 2024)
This research aims to determine the impact of brand image on purchasing decisions for imitation fashion products, focusing on brand image dimensions such as brand association strength, uniqueness, and favorability. The purchasing decision factors examined include product loyalty, purchasing habits, recommending to others, and repeat purchases. A survey method with a quantitative approach was employed, and data were analyzed using the Chi-Square method. The findings indicate that the most significant brand image factor is the favorability of brand association, contributing 52%, while purchasing habits exert the greatest influence on purchasing decisions, accounting for 61.6%. The data analysis revealed a value of 0.00 < 0.05, indicating a significant correlation between brand image and purchasing decisions. For every 1% improvement in brand image, purchasing decisions increase by 20.275%.